IMPLEMENTATION BARRIERS TO HONORING OLDER ADULT PREFERENCES FOR CARE AND EVERYDAY LIVING. (11th November 2018) - Van Haitsma, K S; Kolanowski, A M
Abstract: Person-centered care is widely recognized as the optimal approach to caring for older individuals receiving care in long term service and support settings. One foundational element to person-centeredness is knowing and honoring an older adults' preferences for everyday living. The Preferences for Everyday Living Inventory (PELI) is one tool designed to help facilitate preference based living via assessment of important older adult preferences and supporting fulfillment in everyday care activities. This symposium explores barriers and solutions to a wide variety of approaches utilizing the PELI as a tool to understand and enhance preference based care. The first paper explores a host of barriers encountered when creating a culturally sensitive translation of the PELI into German for use in three different settings of care. The second paper explicates barriers to food preferences from the perspective of 255 older adults residing in nursing homes revealing a total of 381 perceived barriers to fulfilling preferences related to food. The third paper discusses initial results from a pay for performance program in the state of Ohio that utilizes the PELI as a quality indicator. This paper will discuss the barriers encountered by 964 nursing homes seeking to implement the PELI as a part of this state's quality initiative. The final paper will present an innovative approach to addressing the significant barrier of number of preferences held by older adults through the use of a machine learning recommender system. The implications of these papers for research and practice will be discussed.